A Pilot Study on the influence of fatigue on kicking velocity in the soccer players - Ferraz, R.; van den Tillaar, R.; Ferraz, S.; Santos, A.; Mendes, R.; Marinho, D. A.; Cretu, M.; Marques, M. C. (Journal of Physical Education and Sport, 2011)
Problem Statement: Soccer is a game in which fatigue could influence player's performance. The aim of the present study was to evaluate the effect of fatigue, induced acutely, by a specifically soccer activities circuit on kicking velocity. Approach: Nine experienced male soccer players performed prior and after the implementation of an intensive and intermittent exercise protocol maximal instep kicks. Results: Analysis of variance designs with repeated measures indicated a significant difference (p<0.05) in the kicking velocity before and after performing the circuit. Conclusions/Recommendations: The present`s results confirmed the initial hypothesis of the negative influence of fatigue on velocity of the kicking soccer.